Levels of alpha-fetoprotein in amniotic fluids of mice (curly-tail) with neural tube defects. Issue 6 (December 1976) - Adinolfi, M; Beck, S; Embury, S; Polani, P E; Seller, M J
Abstract : Mutant curly-tail mice are genetically predisposed to produce offspring with neural tube defects. Estimation of alpha-fetoprotein in the amniotic fluid of fetuses of these mutants has shown that the levels are raised in fetuses with exencephaly and open spina bifida. This suggests that these mice are a valid model for studies of the aetiology and genesis of neural tube defects in man.